2010
DOI: 10.1200/jco.2009.24.0333
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Trial of Vinorelbine Plus Cisplatin Compared With Observation in Completely Resected Stage IB and II Non–Small-Cell Lung Cancer: Updated Survival Analysis of JBR-10

Abstract: PURPOSE Adjuvant cisplatin-based chemotherapy (ACT) is now an accepted standard for completely resected stage II and III A non-small-cell lung cancer (NSCLC). Long-term follow-up is important to document persistent benefit and late toxicity. We report here updated overall survival (OS) and disease-specific survival (DSS) data. PATIENTS AND METHODS Patients with completely resected stage IB (T2N0, n = 219) or II (T1-2N1, n = 263) NSCLC were randomly assigned to receive 4 cycles of vinorelbine/cisplatin or obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
237
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(261 citation statements)
references
References 23 publications
6
237
0
12
Order By: Relevance
“…30 These recommendations are based on multiple phase 3 trials that compared cisplatin-based doublets with observation after surgical resection. 11,12,31 A large meta-analysis of these trials, the LACE meta-analysis, 15 13 treatment was limited to patients with resected stage IB disease only. Although the combination of carboplatin and paclitaxel was associated with a 17% decrease in the risk of death, this finding did not reach statistical significance (HR, 0.83; 95% CI, 0.64-1.08 [P 5.12]).…”
Section: Discussionmentioning
confidence: 99%
“…30 These recommendations are based on multiple phase 3 trials that compared cisplatin-based doublets with observation after surgical resection. 11,12,31 A large meta-analysis of these trials, the LACE meta-analysis, 15 13 treatment was limited to patients with resected stage IB disease only. Although the combination of carboplatin and paclitaxel was associated with a 17% decrease in the risk of death, this finding did not reach statistical significance (HR, 0.83; 95% CI, 0.64-1.08 [P 5.12]).…”
Section: Discussionmentioning
confidence: 99%
“…(12,13) Unlike the study conducted by Arriagada et al, (11) those two other studies produced promising results: an improvement in survival was confirmed after a long follow-up period. In another study, (14) this improvement was 11% after more than nine years of follow-up, which is in disagreement with the findings of the Arriagada et al study. (11) In addition, in a recent meta-analysis, (15) extremely positive results were obtained with the cisplatinvinorelbine combination, with a reduction in the overall mortality rate of 8.9% in comparison with observation (hazard ratio [HR] = 0.80; 95% CI: 0.70-0.91; p < 0.001).…”
mentioning
confidence: 60%
“…The positive advantage reported in our study also related to higher chemotherapy compliance and more stringent inclusion criteria. The majority of patients received at least 4 cycles of the NP regimen and had a median number of 4.8 cycles (range 1 to 8.4), which was greater than in the previous trials (Arriagada et al, 2004;Butts et al, 2010). In addition, the positive outcome may stem from a restrict criteria for enrolling patients.…”
Section: Discussionmentioning
confidence: 91%
“…The CALGB 9633 trial results in a similar finding (Strauss et al, 2008). Furthermore, the ANITA (Adjuvant Navelbine International Trialist Association) and JBR-10 (National Cancer Institute of Canada Clinical Trial Group) trials also confirm the survival benefit of adjuvant cisplatinvinorelbine chemotherapy in patients with NSCLC at I-IIIA even after follow-up for 9.3 years (Winton et al, 2005;Douillard et al, 2006;Butts et al, 2010). In addition, the LACE (Lung Adjuvant Cisplatin Evaluation) collaborative group and ISA (Italian Survey on adjuvant treatment trial) independently confirm that the effect of NP treatment was significantly better than that of platinumbased combination Douillard et al, 2010;Banna et al, 2011).…”
Section: Introductionmentioning
confidence: 86%